ELECTRICAL CROSSTALK REDUCTION IN HIGH SENSITIVITY MIXED-MODE SIP AND SOC - kim, sungil (The Graduate School, Ajou University, 2008)
Electrical crosstalk is important for both the system-in-a-package (SIP) and system-on-a-chip (SOC) applications because it possesses a key technology for mixed-mode circuits. I characterized the electrical crosstalk phenomena in several devices, including a 1.25 Gb/s optoelectronic (OE) full-triplex transceiver (triplexer) module SIP, a 1.25 Gb/s OE monolithic bi-directional (M-BiDi) SOC, and a mm-wave SOC, and I have proposed a scheme to suppress electrical crosstalk.Electrical crosstalk is important for both the system-in-a-package (SIP) and system-on-a-chip (SOC) applications because it possesses a key technology for mixedmode circuits. I characterized the electrical crosstalk phenomena in several devices, including a 1.25 Gb/s optoelectronic (OE) full-triplex transceiver (triplexer) module SIP, a 1.25 Gb/s OE monolithic bi-directional (M-BiDi) SOC, and a mm-wave SOC, and I have proposed a scheme to suppress electrical crosstalk. First, the 1.25 Gb/s OE triplexer module SIP with planar-lightwave-circuits (PLC) was designed and fabricated for fiber-to-the-home (FTTH) services according to gigabit/ethernet-passive optical networks (G/E-PONs) standards. Low electrical crosstalk is critical for reliable operation of the 1.25 Gb/s OE triplexer module SIP. It has been intensively investigated because electrical crosstalk on a resistive silicon substrate is more serious than that on a dielectric substrate. The transmitter and receiver performances satisfied their specifications defined in the standards. The proposed module layout has a convenient design convenience and greatly reduces the silicon substrate size (about 50 %). Using the proposed layout, the 1.25 Gb/s OE triplexer module SIP was fabricated with electrical and mechanical packaging technologies with low electrical crosstalk design and passive alignment method. It was then verified its validity by dynamic performance including the bit error rate (BER) and an eye diagram. The reduction of electrical crosstalk is also one of the key technologies in design and fabrication of mixed-mode SOCs like the 1.25 Gb/s OE M-BiDi SOC for 1.25 Gb/s FTTH services and the mm-wave SOC for 60 GHz wireless personal area network (60 GHz WPAN SOC). This is because it has become more important to increase SOC reliabilities such as receiver sensitivity and BER. Electrical crosstalk in these SOCs many occurs because of the substrate coupling effects. To reduce electrical crosstalk, I analyzed and measured the substrate coupling effects with various isolation techniques, such as a trenched and implanted structure. To satisfy the signal-to-noise ratio (SNR) of the mixed-mode SOCs, including the 1.25 Gb/s OE M-BiDi SOC and 60 GHz WPAN SOC, the implanted structure has the lower substrate coupling effects than the others based on analytical and measured results. I also derived equivalent circuits, which can be helpful in the design and fabrication of the 1.25 Gb/s OE M-BiDi SOC and 60 GHz WPAN SOC. Consequently, I analyzed and measured electrical crosstalk phenomena to increase the stability of the module SIP and SOC, and proposed electrical crosstalk suppression methods such as the dummy ground structure and the implant isolation technique.
학위논문(박사)--아주대학교 일반대학원 :컴퓨터공학,2008. 2
Keywords: Electrical; crosstalkreduction; high sensitivitymixed-mode; sip; soc